2013
DOI: 10.1371/journal.pgen.1003288
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 Co-Occupies Distal Enhancer Elements with Distinct POU Factors in ESCs and NPCs to Specify Cell State

Abstract: SOX2 is a master regulator of both pluripotent embryonic stem cells (ESCs) and multipotent neural progenitor cells (NPCs); however, we currently lack a detailed understanding of how SOX2 controls these distinct stem cell populations. Here we show by genome-wide analysis that, while SOX2 bound to a distinct set of gene promoters in ESCs and NPCs, the majority of regions coincided with unique distal enhancer elements, important cis-acting regulators of tissue-specific gene expression programs. Notably, SOX2 boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
191
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(209 citation statements)
references
References 139 publications
(170 reference statements)
17
191
1
Order By: Relevance
“…References for ChIP‐Seq data sets are in order (left to right): Oct2 in B cells 39, Brn2 after 48 h of its overexpression in MEFs 54, Brn2 in NPCs 54, Brn2 in NPCs 55, and Oct4 in ESCs 72. The upper panel was generated using word searches with IUPAC strings instead of pwms on the same set of ChIPseq peaks as in the lower panel.…”
Section: Resultsmentioning
confidence: 99%
“…References for ChIP‐Seq data sets are in order (left to right): Oct2 in B cells 39, Brn2 after 48 h of its overexpression in MEFs 54, Brn2 in NPCs 54, Brn2 in NPCs 55, and Oct4 in ESCs 72. The upper panel was generated using word searches with IUPAC strings instead of pwms on the same set of ChIPseq peaks as in the lower panel.…”
Section: Resultsmentioning
confidence: 99%
“…We next used published Sox2 ChIP-seq data from mESCs and mNPCs [7] and data generated from hESCs and hNPCs in this study to compare the regulatory network of SOX2 between mouse and human and found some species-specific features. For example, common SOX2 PBGs for hESCs and hNPCs were most significantly enriched in RNA metabolic processes, RNA splicing as well as chromatin organization ( Figure 1D).…”
Section: Conserved and Divergent Transcription Programs Governed By Smentioning
confidence: 99%
“…Apart from these studies, how SOX2 exerts cell type-dependent roles in these two distinct and developmentally related cell types is largely unknown. Comparative studies of Sox2-binding motifs in mouse ESCs (mESCs) and mouse NPCs (mNPCs) have led to the identification of Pou3f2 as an mNPC-specific Pou family member that is extensively colocalized with Sox2 [7]. However, a recent study challenges the functional association between the two factors in mNPCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of an organ development is manifested through spatiotemporal expression of genes involved in development, which is tightly regulated to a large extent by the combination of transcription factors in multi-protein complexes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In these processes, the binding affinity of transcription factors to their genetic elements, which is crucial for transcription activity, is modulated by cooperative binding: low inherent binding affinity of the individual factors is largely enhanced when they present together by their synergistic action.…”
Section: Introductionmentioning
confidence: 99%
“…One example that shows this plasticity and diverse combinatorial transcription activity is Sox2, which activates its downstream transcriptional targets by forming cooperative complex with various factors in each developmental stage. For example, it maintains pluripotency by partnering with various factors like Oct4 and Nanog (5,7,(11)(12), and controls neurogenesis and retinal developmental by forming complexes with Pax6 (7-10), Otx2 (11), Tlx (12) or Brn2 (13). Therefore, it is essential to investigate the dynamics of their cooperativity to understand functional intricacies involved in the process of transcription.…”
Section: Introductionmentioning
confidence: 99%